Developing a model of marital adjustment based on self-compassion, marital intimacy and job satisfaction in married female teachers - Bakhshi, Shokoofeh; Sadeghi, Masoud (Psychology of Woman Journal, 2023)
Objective: The present study aimed to evaluate the marital adjustment model based on the factors of marital intimacy, self-compassion and job satisfaction. The research design was a correlation of component-based structural equation modeling. Method: The statistical population was all married female teachers of high schools in Khorramabad city in 2021 -2022. The sampling method was a multi-stage cluster sampling in which 100 married female teachers responded to the scales of Dyadic Adjustment Scale (DAS), Marital Intimacy Scale (MIS), Self-Compassion Scale (SCS), and Minnesota Satisfaction Questionnaire (MSQ). In order to analyze the data, SPSS 23 software was used for descriptive statistics, and PLS software was used to evaluate the model’s fit. Results: The research findings showed that the model has a high fit and that the predictive power of the model is appropriate. Among the variables, marital intimacy, with a factor loading of 0.68, has the greatest impact on marital adjustment, and the variables of self-compassion and job satisfaction, with factor loadings of 0.165 and 0.160, are in the second and third positions, respectively. Conclusion: The results showed that self-learning variables marital intimacy and job satisfaction positively and significantly affect marital adjustment.